Desktop Calculator for Multiple Analysis of Environmental Risk - Cáceres, Lorena (2022)
Anthropic activities have a significant influence on the environment, from the extraction of raw materials to the environmental impact generated by the processes developed and products manufactured. For this reason, rigorous control of the exploitation of resources must be introduced and industrial processes optimized to achieve efficiency in using raw materials and energy consumption through evaluating environmental risks with a life cycle approach. This work aims to design an application that allows assessing the environmental risks generated by a productive activity. The advantages of this proposal are the reduction of costs based on the quantification of resources used and the comparative analysis of the results with reference limits cited in national and international regulations, which allow decision-making to minimize environmental impact. As a result of this research, a calculator was obtained, which is executed from a user interface allowing the calculation of the most significant environmental risks in terms of CO2 emissions, wastewater, and waste generation associated with production processes under regular conditions, warning conditions, and in emergency situations. Finally, to validate its operation, real data from an industry dedicated to the production of dairy products were applied, obtaining a risk analysis in terms of CO2 emissions and wastewater generation.